2022
DOI: 10.1038/s41467-022-28597-x
|View full text |Cite
|
Sign up to set email alerts
|

TRPC3 shapes the ER-mitochondria Ca2+ transfer characterizing tumour-promoting senescence

Abstract: Cellular senescence is implicated in a great number of diseases including cancer. Although alterations in mitochondrial metabolism were reported as senescence drivers, the underlying mechanisms remain elusive. We report the mechanism altering mitochondrial function and OXPHOS in stress-induced senescent fibroblasts. We demonstrate that TRPC3 protein, acting as a controller of mitochondrial Ca2+ load via negative regulation of IP3 receptor-mediated Ca2+ release, is down regulated in senescence regardless of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Together with other works which reported increased Ca 2+ levels in several senescence contexts [ 5 , 8 , 9 , 10 , 11 ], our observations suggest that a rise in intracellular Ca 2+ contents could be a new hallmark of cellular senescence. Although some contributions of Ca 2+ in senescence have already been identified, its precise role in this context is not fully understood yet [ 5 , 8 , 9 , 10 , 11 ]. In our study, we observed an increase in Ca 2+ contents both in the cytosol and in intracellular stocks, which are mainly in the ER and in the mitochondria.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Together with other works which reported increased Ca 2+ levels in several senescence contexts [ 5 , 8 , 9 , 10 , 11 ], our observations suggest that a rise in intracellular Ca 2+ contents could be a new hallmark of cellular senescence. Although some contributions of Ca 2+ in senescence have already been identified, its precise role in this context is not fully understood yet [ 5 , 8 , 9 , 10 , 11 ]. In our study, we observed an increase in Ca 2+ contents both in the cytosol and in intracellular stocks, which are mainly in the ER and in the mitochondria.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, as an increase in intracellular Ca 2+ contents appears to be a common mark of senescence based on our data in epithelial cells ( Figure 1 ) and on data in other cell types according to previous reports [ 6 , 7 , 11 ], we investigated whether induction of the expression of calcium-buffering calbindin-type proteins could also be a common mark of senescent cells. In addition to Raf and Mek oncogenes, bleomycin, and nutlin ( Figure 1 ), other senescence inducers such as Ras oncogene activation, H 2 O 2 , TGFβ, or KCl, which are all known to induce senescence in HMECT [ 14 , 19 , 20 , 21 ], also triggered a rise in CALB1 expression in HMECT ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Mitochondrial mass increases in senescence, but this is accompanied by mitochondrial dysfunction and the production of ROS, generating chronic oxidative stress [125,126]. ER-mitochondria contact sites appear critical in senescence regulation [127], and mitochondrial dysfunction and ROS production were shown to be mediated in many senescence models by increased IP3R-mediated mitochondrial calcium uptake from the ER following ITPR downregulation [128]. Oxidative stress induces senescence in many settings [129,130], but the upregulation of ROS detoxifying systems is also critical for the decision to undergo senescence over apoptosis [126].…”
Section: Class III Senolytics: Further Disturbing Cellular Homeostati...mentioning
confidence: 99%